IMPROVING ELEMENTARY SCHOOL TEACHERS' KNOWLEDGE REGARDING IDENTIFICATION RECORDING AND STUDENTS’ PERSONAL HEALTH RECORDING AT SDN KAMPUNG DALEM 6 KEDIRI - Rimawati; Muhamad Liswansyah Pratama (Suluh Adiluhung Publisher (SAPub), 2024)
Medical Records in the world of education are very important to be implemented in terms of administrative and documentation aspects. In terms of administration, the existence of health records can make it easier for teachers or principals to store and search for files related to the health of their students, while in documentation it can make it easier for teachers to find out the health history of students. The purpose of this study was to identify elementary school teachers' knowledge about students’ personal health records at SDN Kampung Dalem 6 Kediri. This study used a simple descriptive design with a collection tool in the form of a questionnaire. The study was conducted at SDN Kampung Dalem 6 Kediri with total sample of 13 respondents. Samples were taken using the training, technical guidance, facilitation approach methods. The results of the study showed that more than half of the respondents (69.20%) had high knowledge about personal health records and the rest (31.80%) had moderate knowledge. The recommendation of this study is to conduct further research by increasing the number of respondents.